Penerapan Model Pembelajaran Video Based Learning (VBL) untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran IPA Kelas VII di SMP IT Najib Rasyid - Pratomi, Yogi; Setiawan, Dena Latif (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to determine the effect of implementing the Video Based Learning model combined with the interactive media Animaker on students' learning outcomes. The research method used is a quantitative research method with a Quasi-Experimental Design approach. The research sample consists of students from class VII at SMP IT Najib Rasyid. The population of this study is all seventh-grade students at SMP IT Najib Rasyid, totaling 83 students. The research sample is taken from classes VII A and VII B, with a total sample of 54 students. The research instruments include a learning outcome test and a questionnaire. The data analysis techniques used are normality test, homogeneity test, hypothesis testing, validity test, reliability test, and data tabulation test. The results of this study indicate that (1) The application of the video-based learning model using animation videos based on Animaker can improve students' learning outcomes. This is evidenced by the post-test results of the experimental class being higher than that of the control class. (2) Based on the hypothesis test results, the average score of the pre-test and post-test of 32.828 is much higher compared to the control class (VII B) which only scored 11.52. Thus, the alternative hypothesis (H₁) is accepted and the null hypothesis (H₀) is rejected. (3) Students' responses to the implementation of the VBL model are very positive, as evidenced by the student satisfaction questionnaire results which reached an average score of 92.64. This indicates that students feel satisfied and interested in learning using Animaker-based video media.